Trends and challenges in earthworks for transportation infrastructures - Correia, A. Gomes (2012)
Advances in Transportation Geotechnics II deals with the geotechnics of roads, railways and airfields. Providing economic and sustainable transportation infrastructures for societies is highly dependent on progress made in this field. These contributions to the 2nd International Conference on Transportation Geotechnics (Hokkaido, Japan, 10-12 September 2012), held under the auspices of the International Society of Soil Mechanics and Geotechnical Engineering (ISSMGE), cover a broad range of technical topics, including those addressed by the first conference held in Nottingham, UK in 2008.